A multi-case study of entrepreneurial competencies in microenterprises - Tzu-Jiun Yeh; Hung-Jung Chang (International Journal of Management, Economics and Social Sciences (IJMESS), 2018)
Building on a theoretical framework of integrated entrepreneurial competencies with substantial literature supported by Baron and Ensley (2006), Bartlett and Ghoshal (1997), Karra, Nelson and Tracey (2008), Man, Lau and Chan (2002), and McGregor et al. (2000), this study conceptually interpreted a framework of entrepreneurial competencies in microenterprises through conducting a multi-case qualitative method. By collecting and analyzing related documentation, reviewing literature, and observing researchers' observations and participants involved the study identified six key entrepreneurial competencies in microenterprises i.e., opportunity exploration competencies, opportunity exploitation competencies, organizing competencies, strategic competencies, relationship competencies, and commitment competencies. As a result, the researchers provided the structure for further research for the practice and advancement of micro-entrepreneurship.
Keywords: L26; M13; P42; 330; Microenterprises; entrepreneurial competencies; entrepreneurship; start-up ventures; small and medium enterprises (SMEs)